ASPEK HUKUM DAN PENYELESAIAN SENGKETA HIBAH TANAH DALAM PERSPEKTIF KUHPERDATA DI INDONESIA ATAS PUTUSAN PENGADILAN NEGERI NOMOR 109/Pdt.G/2009/PN.MTR DAN 17/Pdt.G/2021/PN.Klb - RAHMAN, ASEP AULIA (Fakultas Hukum Universitas Narotama, 2026)
This study aims to analyze the legal aspects of land grants (hibah tanah) within the framework of the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata or KUHPerdata), with particular emphasis on two judicial decisions: District Court of Mataram Decision No. 109/Pdt.G/2009/PN.MTR and District Court of Kalabahi Decision No. 17/Pdt.G/2021/PN.Klb. The research adopts a normative legal method using statutory, conceptual, and case approaches. The findings reveal that although both courts relied on the same legal provisions of the Civil Code, their reasoning diverged significantly. The Mataram court prioritized formal validity and the evidentiary strength of the notarial deed, reflecting a legal-formalist orientation. In contrast, the Kalabahi court annulled part of the grant to safeguard the legitime portie, thereby emphasizing substantive justice and protection of heirs’ rights. This divergence highlights the lack of consistency in the judicial application of inheritance and land grant provisions, which in turn undermines legal certainty. The study argues that harmonization of jurisprudence is essential to balance legal certainty with fairness, ensuring that land grant disputes are resolved not only in line with formal legal rules but also with sensitivity to social justice and familial equity. Keywords: land grant, Indonesian Civil Code, legitime portie, land dispute, comparative judgment